Teachers' Centers Exchange. Directory Supplement 1978 - Lance, Jeanne; Piper, Barbara; Far West Lab. for Educational Research and Development, San Francisco, CA. ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
In this supplement to a previously published Teachers' Center Exchange Directory (April 1977), 55 additional teacher centers are described. These descriptions include the name of the contact person at each center, the program offered, resources, staff, participation, fees and credit, affiliation, support, decision making, and publications. (JD)
Availability: Far West Laboratory, 1855 Folsom Street, San Francisco, CA 94103 ($6.00).
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
ERIC Note: For related document, see ED 150 112.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Directories; Financial Support; Governance; Information Sources; Inservice Education; Inservice Teacher Education; Program Descriptions; Resource Centers; Teacher Centers; Reference Materials, Directories/Catalogs.